Robust assembly strategy of a timing belt in the belt drive unit against its shape uncertainty with a single parallel jaw gripper. (3rd May 2022) - Nishimura, Kazuki; Dobashi, Hiroki
Abstract : In a versatile robotic assembly system in manufacturing, robots need to assemble parts with various shapes and materials. In general, the assembly of flexible parts such as rubber belts is difficult. In particular, the assembly of a timing belt is hard because it has the following three characteristic properties. First, it has flexibility. Second, it can hardly be stretched by tension. Third, its shape is uncertain due to an individual difference and influence by grasping positions. Targeting the belt drive unit in the World Robot Summit 2018, this paper presents a robust strategy for assembling a timing belt to a set of pulleys with a single conventional parallel jaw gripper against such shape uncertainty. The validity and the utility of the proposed strategy are experimentally verified. GRAPHICAL ABSTRACT: UF0001